Kajian Risiko dan Manfaat Implementasi Internet of Things (IoT) Pada Pengelolaan Energi Listrik Berbasis Smart Grid - Saiful Arifin, Muhammad; Ilham (AMIK STIEKOM SUMATERA UTARA, 2024)
The application of the Internet of Things (IoT) in smart grid-based electricity management offers great potential to enhance operational efficiency, system reliability, and environmental sustainability. IoT technology enables devices and sensors to connect and communicate in real-time. This creates a smart electricity grid that can collect accurate data, analyze energy consumption patterns, and support optimal resource management. This reduces energy waste, integrates renewable energy sources such as solar and wind power, and significantly contributes to the reduction of CO2 emissions. Additionally, IoT gives consumers greater control in monitoring and managing their energy consumption through technologies such as smart meters and cloud-based energy management systems. However, the implementation of this technology also faces various challenges, particularly related to cybersecurity threats, high initial investments, and the need for appropriate infrastructure. This research uses literature review techniques to investigate the benefits and risks of IoT implementation in smart grid systems. The research shows that cybersecurity threats such as data breaches and energy theft are one of the main obstacles that need to be addressed through security technologies such as data encryption, intrusion detection, and the development of blockchain-based security protocols. In addition, the high costs of procuring IoT hardware and software require government policy support and joint public-private sector investment. This study concludes that with the right approach, the implementation of IoT on smart grids can become a strategic solution for building a more efficient, environmentally friendly, and sustainable energy system. The recommendations provided include strengthening regulations, raising public awareness, and developing security technologies to minimize existing risks. Therefore, IoT can be the main catalyst for transforming the energy sector towards a more environmentally friendly and efficient future.